Degrowth – A Transcendence of Sensate Cultural Mentality? P. Sorokin and His Theory of Social Change as a Strategy Towards Socio-Ecological Transformation - Klanjšek, Rudi (Komuniciranje okoljske krize, 2025)
There are essentially two fundamental models that explain patterns of social change: the linear model, based on evolutionary theory, and the cyclical model, which posits that human societies, much like many other phenomena, undergo recurring cycles of development. As linear models of “eternal progress,” rooted in the Enlightenment project, have come to dominate interpretations of human history and social transformation, the relevance of cyclical models warrants renewed examination. This study focuses on the cyclical model of social change developed by Pitirim Sorokin, evaluating the concept of degrowth as an indicator of the “progressive disintegration of sensate culture, society, and man,” as well as a sign of the “emergence and gradual growth of the first seeds of a new idealistic/ideational sociocultural order” (Sorokin, 1957, Preface). Drawing on Sorokin’s framework and its derived predictions, the study assesses a range of proposals and strategies aimed at transforming the dominant growth-dependent modes of production, living, and communication. Central to this analysis is Jason Hickel’s work Less is More (2020), which serves as a key reference point.